2020
DOI: 10.1108/ijchm-01-2019-0065
|View full text |Cite
|
Sign up to set email alerts
|

Hotel revenue management for the transient segment: taxonomy-based research

Abstract: Purpose This paper aims to (1) organize the open literature on hotel revenue management systems, (2) compare practitioner systems in terms of functionality and (3) integrate (1)-(2) into research stream recommendations for the open literature with an empirical focus. Design/methodology/approach The authors use Nickerson’s taxonomy development method from the field of information systems to build the taxonomy. Findings New forecasting areas include developing a metric for the degree of strategic fit of a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Unlike in the marketing field, a systematic review of pricing studies lacks in H&T literature, even though the research interest is growing. Pricing was briefly discussed in the revenue management literature (Anderson and Xie, 2010; Baker et al , 2020; Denizci Guillet, 2020; Denizci Guillet and Mohammed, 2015; Vives et al , 2018). These review articles identified pricing as one dominant topic in revenue management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike in the marketing field, a systematic review of pricing studies lacks in H&T literature, even though the research interest is growing. Pricing was briefly discussed in the revenue management literature (Anderson and Xie, 2010; Baker et al , 2020; Denizci Guillet, 2020; Denizci Guillet and Mohammed, 2015; Vives et al , 2018). These review articles identified pricing as one dominant topic in revenue management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This emerging trend made H&T pricing research more critical in contributing to academia. However, in the H&T field, pricing was often studied as one subarea of revenue management, which is a research direction that H&T scholars devoted much effort into (Anderson and Xie, 2010; Baker et al , 2020; Denizci Guillet, 2020; Denizci Guillet and Mohammed, 2015; Domingo-Carrillo et al , 2017; Kimes, 2003; Thompson, 2010; Vives et al , 2018). With increasing research attention paid to pricing, a systematic review would help clarify the current states of pricing research and suggest future agendas for H&T scholars.…”
Section: Introductionmentioning
confidence: 99%
“…scale in the context of hospitality generally defined as a management process regarding pricing strategy, demand modeling and forecasting, inventory and price optimization, distribution channel management, and performance evaluation (Baker et al, 2020;Binesh et al, 2021;Denizci Guillet, 2020;Sainaghi, 2020). RMP is therefore the pricing aspect of RM (Ng et al, 2017;Xu et al, 2019).…”
Section: Measurementmentioning
confidence: 99%
“…During the full-text assessment procedure, 10 articles were excluded for the following reasons: Neither collected or analysed online reviews, nor provided hoteliers with practical implications (Ait-Bakrim et al, 2019;Kamboj & Rahman, 2017;Nizamuddin, 2015;Păunescu & Moraru, 2018;Tsaur, Huang & Luoh, 2014). The main focus of the study is to validate or develop an online review related system or algorithm (Xiang, Du, Ma & Fan, 2018), while the focus of the study and managerial implications were related to another type of accommodation (Xu, 2020) and studies were identified as review papers (Baker, Eziz & Harrington, 2019;Kizildag et al, 2017). Finally, 59 articles were considered for this study.…”
Section: Methodsmentioning
confidence: 99%